The Implementation of Drill Methods to Improve Children with Autism's Ability to Tie Shoelaces - Dapa, Aldjon Nixon; Undap, Tiersa; Kiriweno, Henny B.A. (Indonesian Journal of Disability Studies, 2021)
The purpose of this study is to analyze the effectiveness of drill methods in increasing the ability to tie shoelaces to autistic children. The type of research method used in this study is single subject research (SSR), with A-B-A research design. this research was conducted at the SLB Paulus Tomohon. The subjects in this study were autistic students who sat in class X. The results showed that subjects could not follow instructions along baseline A1 in 5 times, baseline B as many asÂ  15 times, and baselin A2 as much as 5 times, Analysis of data at baseline (A1) long conditions 5 sessions with mean level 0, 0% presentation stability. Furthermore, in the intervention stage (B) the condition is 15 sessions long with mean level 6.46 and stability percentage 33%. The baseline stage (A2) with the condition of 5 sessions and mean level 10, the percentage of stability is 100%, with the existing data, it can be concluded that the drill method can improve the ability to tie shoelaces to autistic children in class X at the SLB Paulus Tomohon.